Current-induced spin-orbit torque effective fields in multilayer structures with perpendicular magnetic anisotropy - Engel, Christian (2018)
Current-induced spin-orbit torque (SOT) effects are usually attributed to spin Hall effect (SHE) occuring in an adjacent nonmagnetic heavy metal layer attached to a ferromagnetic metal (FM) layer and Rashba effect at the FM interface. SOT effects currently draw much attention to the research community due to their potential of magnetization switching and magnetic domain wall (DW) driving. While being firstly experimentally observed in the early 2000’s, contradicting results have been reported about the magnitude of SOT effective fields in nominal identical systems, the correlation between dampinglike and fieldlike SOT terms and even unexpected angular dependence behavior of SOT fields with respect to the magnetization direction have been reported which requires further understanding of SOT fields in lateral confined multilayer structures. In this thesis, various properties of several multilayer structures with perpendicular magnetic anisotropy (PMA) have been investigated, notably the influence of magnetization azimuthal variation on SOT effective fields. First, the quantification of SOT effective fields using harmonic Hall voltage technique based on anomalous Hall effect (AHE) only was compared with the in-situ current-induced DW depinning field method of a pinned DW at the Hall cross. This allows for a direct comparison of SOT effective fields which manifests the importance of the planar Hall effect (PHE)-symmetry using the harmonic Hall voltage technique for SOT effective field investigation. Also, coercivity and anisotropy fields have been shown to decrease with increasing current in the magnetic structure which is attributed SOT effects. With the consideration of the PHE-symmetry in the harmonic Hall technique method, an analytical solution for a new measurement approach to quantify SOT effective fields as a function of the magnetization azimuthal angle has been derived and experimentally successfully tested in two inherent different sample stacks with PMA. While usually a negligible azimuthal angular dependence of SOT fields is expected, an unexpected large angular dependence has been found for a Pt/(Co/Ni)2/Co/Ta multilayer stack structure. By exploiting angular symmetries by means of Fourier series expansion of 4 th order which replicates any periodic signal due to its property of the orthogonal functionality, − sin 2ϕ and − cos 4ϕ dependencies of the SOT fields with respect to the magnetization azimuthal angle have been found. A large angular dependent field offset in the first harmonic Hall voltage has also been observed. Suggesting a unidirectional in-plane exchange bias (EB)-like field, a formula for the angular dependence of v the field offset is derived which is well fitted to the data values and confirms the unidirectional EB field in the Pt/(Co/Ni)2/Co/Ta structure, which does not exhibit the usually required antiferromagnetic/FM layers interface. The in-plane EB field is attributed to the composition of the FM/FM multilayer structure with large/low magnetocrystalline anisotropy constants in combination with the amorphous Ta capping layer controlling the grain size of the polycrystalline heterostructure. The anisotropy field, HK, also exhibits an angular dependence with spikes at azimuthal angles 45◦ and 225◦. This is mainly attributed to the reorientation in field offset direction at these angles as well as intrinsic anisotropy transformations within the structure, as observed by the change in DW depinning directions and small uncertainties in the determination of the Hall resistance ratio of PHE/spin Hall magnetoresistance (SMR) to AHE resistances. The computation of the anisotropy and SOT fields detection also reveal no influence due to EB-like field which proposes any correlation of SOT, HK, SMR and EB must be intrinsically related via spin-orbit coupling (SOC).